Crucible of light: Islam and the forging of Europe from the 8th to the 21st century - Drayson, Elizabeth (Picador, 2025)
"In Crucible of Light, Elizabeth Drayson pulls together the epic interwoven history of the Muslim and Christian worlds over an 800-year span, taking in the conquest and re-conquest of Spain, the meteoric rise of Arabo-Norman Sicily, the Ottoman renaissance of the 16th to 18th centuries, the ebb and flow of Balkan history and the fate of contested islands like Cyprus and Malta, with their very different outcomes. Focusing on major turning points, individual stories and key places, from Mecca to Cordoba, from Damascus to Venice, and from Vienna to Istanbul, Drayson tracks the themes that unite us - classical learning preserved in Islamic libraries, the enduring influence of Moorish architecture and design, the food we share, the goods we have traded and the continuing discourse between individuals and cultures that has permeated Europe's history and shaped its borders. Drayson also explores the growing dialogue between Muslims and Christians across Europe today, a dialogue prefigured in the history of medieval and early modern Europe, in which harmony and enlightenment rise above perennial conflicts. These ideas challenge the way contemporary European identity is defined and point to the vital impact of Islamic civilization upon the continent. Surprisingly few people are aware of how much Europe owes to its Islamic heritage except via pockets of tourism, and this book aims to correct that while exploring the endless complexities that this vexed relationship throws up. At a time when Islam is so narrowly identified with terrorism and migration in Europe it is a necessary corrective"--publisher's description